AUDIT ENERGI LISTRIK PADA GEDUNG PLASA TELKOM TEUKU UMAR DENPASAR - Rahmawati, Ayu; Suartika, I Made; Manuaba, Ida Bagus Gede (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p18, 2022)
The increasing need for electrical energy every year results in the availability of energy sources is dwindling. Therefore, the need for energy conservation to streamline the use of electrical energy without reducing its comfort or productivity. The main factor of energy conservation is energy auditing. Plasa Telkom Teuku Umar is a company engaged in telecommunications. The convenience of employees and customers takes precedence over this0company.0The best service0must also be followed by the efficient use of facilities. For this reason, an electrical energy audit is needed. In this study, it was attached0to the air0conditioning0system and lighting system. It is attached to the air conditioning system and lighting system. Tools0that can be0used for measurement in the field are Lux Meter, (light intensity measurement), Tang Ampere (electric current measurement), and Thermometer (room temperature measurement). The study was conducted by0calculating and comparing0electrical energy consumption in lighting and air conditioning systems between before and after an energy audit. Calculate the pre- and post-audit IKE (Energy Consumption Intensity) and compare it to the IKE standard. The results of the study found energy savings of 36.06%. From electricity usage of 16.86 kWh/m2/bln pre audit to 10.78 kWh/m2/mo post audit.